Research on the Construction Method of Cultural Visiting Routes Based on the Coupling Coordination Degree Model: A Case Study of Zhongshan Road Historical and Cultural Block, Xiamen, China - Yue Cai; Mengru Zhou; Quhang Wu (Buildings, 2024)
As a form of urban experience tour, cultural visiting routes provide an innovative approach to addressing the fragmentation and isolation of cultural resources in historic districts. This method emphasizes the systematic continuity of cultural spatial patterns and is currently implemented at both regional and urban scales. However, methods for constructing cultural visiting routes at the block scale still require further investigation. And there is a notable lack of studies that consider the integration of multiple systems in cultural visiting routes. Consequently, this research proposes a novel approach for constructing cultural visiting routes based on the coupling and coordination of multiple systems. Using the Zhongshan Road Historical and Cultural Block in Xiamen, China, as a case study, this study develops cultural visiting routes by analyzing the degree of coupling coordination between cultural resource value and the street walking environment. The findings are as follows: (1) The cultural visiting routes within the Zhongshan Road Block can be categorized into three levels: the first-level routes, represented by Zhongshan Road; the second-level routes, represented by Datong Road; and the third-level routes, represented by Park South Road. (2) The first-level cultural visiting routes demonstrate a high degree of coupling coordination, with an optimization direction focused on refined updates. The second-level routes exhibit a medium degree of coupling coordination, indicating an urgent need to address issues across the entire road section. The third-level routes reveal a low degree of coupling coordination, necessitating attention to the enhancement of cultural visiting elements. This study emphasizes that the construction of block-scale cultural visiting routes must prioritize not only the extraction of value from cultural resources but also the influence of the street walking environment.